The Use of Mother Tongue in Teaching and Learning of Second Language (English) at the Higher Secondary Level in Islamabad Hazrat Umar Abstract The role of the mother tongue as a medium of instruction is an important issue in second language teaching a - Hazrat Umar (JCTE, 2023)
The role of the mother tongue as a medium of instruction is an important issue in second language teaching and learning and needs to be researched. The objective of this study is to investigate the use of the mother tongue in teaching and learning of second language, in this case the teaching and learning of English language at the Higher Secondary level at the Federal Government Educational Institutions in the capital territory of Islamabad.